Simultaneous Lightwave Information and Power Transfer in 6G Networks - Papanikolaou, Vasileios; Tegos, Sotiris A.; Palitharathna, Kapila W.S.; Diamantoulakis, Panagiotis D.; Suraweera, Himal A.; Khalighi, Mohammad Ali; Karagiannidis, George K. (IEEE Communications Magazine, 2024)
The evolution of wireless networks toward the sixth generation (6G), and the inclusion of novel application-Aware features characterized by sustainability requirements, call for the use of energy-efficient communication technologies, where optical wireless communications can play an important role. In the quest for sustainability, battery recharging through energy harvesting (EH) has also attracted considerable attention. A promising approach consists in combining data transmission and EH into a single scheme, namely, simultaneous lightwave information and power transfer (SLIPT), which capitalizes on the technological maturity and efficiency of optical transceivers to ensure both functionalities. In this article, we investigate SLIPT as a potential technology to help achieve the sustainability goals of 6G by discussing SLIPT transceiver architectures, optical beam propagation, and fundamental design trade-offs. We also categorize the applications of SLIPT with respect to range-from very short to long range-considering indoor, underwater, and aerial scenarios, and present its synergy with other popular technologies that are envisioned for use in 6G networks, for example, artificial intelligence, reconfigurable intelligent surfaces, and quantum communications.
CRIS-Team Scopus Importer:2024-03-22